Training sessions with tackles impair upper-limb neuromuscular function in elite rugby union - Brustio, Paolo Riccardo; Boccia, Gennaro; Ungureanu, Alexandru; Lupo, Corrado (Biology of Sport, 2020)
The aim of this study was to investigate the response to non-tackle and tackle field-based training on upper- and lower-limb neuromuscular function in elite rugby union players. Nine elite senior elite rugby union players (mean age = 21 ± 2 years; height = 184 ± 7 cm; body mass 91.0 ± 9 kg) were evaluated before and immediately following 17 training sessions. A total of 306 assessments were performed. Data on neuromuscular function of plyometric push-up and countermovement jump were calculated from force signals using inverse dynamics. The change from pre- to post-session was investigated across non-tackle and tackle training using a linear mixed model. Considering upper-limb neuromuscular function, peak concentric power [P = 0.024; ES = 0.33 95%CI (0.04, 0.62)] was significantly lower after tackle compared to non-tackle training. In addition, peak countermovement jump eccentric power was significantly lower after non-tackle compared to tackle training [P = 0.044; ES = -0.4 95%CI (-0.69, -0.1)] in lower-limb neuromuscular function. Overall, the results indicated that the type of training influences upper- and lower-limb neuromuscular function differently immediately after training. Indeed, due to physical contact, the upper-body neuromuscular function increased during tackle training. In contrast, lower-body neuromuscular function emerged only in non-tackle training, due to the greater distance covered during this type of training session. Coaches and practitioners should plan adequate weekly training sessions according to this information.